The single-use rhinolaryngoscope: an evaluation and cost comparison. Issue 9 (28th September 2020) - Mistry, R; Russell, R V; Walker, N; Ofo, E
Abstract: Background: This study investigated whether the single-use rhinolaryngoscope is clinically and economically comparable to the conventional reusable rhinolaryngoscope within a tertiary otolaryngology centre in the UK. Methods: A non-blinded, prospective and single-arm evaluation was carried out over a 5-day period, in which micro-costing was used to compare single-use rhinolaryngoscopes with reusable rhinolaryngoscopes. Results: Overall, 68 per cent of the investigators perceived the single-use rhinolaryngoscope to be 'good' or 'very good', while 85 per cent believed the single-use rhinolaryngoscope could replace the reusable rhinolaryngoscope ( n = 59). The incremental costs of reusable rhinolaryngoscope eyepieces and videoscopes in the out-patient clinic, when compared to single-use rhinolaryngoscopes, were £30 and £11, respectively. The incremental costs of reusable rhinolaryngoscope eyepieces and videoscopes in the acute surgical assessment unit, when compared to single-use rhinolaryngoscopes, were −£4 and −£73, respectively. Conclusion: The single-use rhinolaryngoscope provides a clinically comparable, and potentially cost-minimising, alternative to the reusable rhinolaryngoscope for use in the acute surgical assessment unit of our hospital.